7(4x+7)=3+4(-4-6x)

Simple and best practice solution for 7(4x+7)=3+4(-4-6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(4x+7)=3+4(-4-6x) equation:



7(4x+7)=3+4(-4-6x)
We move all terms to the left:
7(4x+7)-(3+4(-4-6x))=0
We add all the numbers together, and all the variables
7(4x+7)-(3+4(-6x-4))=0
We multiply parentheses
28x-(3+4(-6x-4))+49=0
We calculate terms in parentheses: -(3+4(-6x-4)), so:
3+4(-6x-4)
determiningTheFunctionDomain 4(-6x-4)+3
We multiply parentheses
-24x-16+3
We add all the numbers together, and all the variables
-24x-13
Back to the equation:
-(-24x-13)
We get rid of parentheses
28x+24x+13+49=0
We add all the numbers together, and all the variables
52x+62=0
We move all terms containing x to the left, all other terms to the right
52x=-62
x=-62/52
x=-1+5/26

See similar equations:

| -4(u+6)=-6u-22 | | 7(b-90)=35 | | X2+5x-32=2x-4 | | -5/6x-1/9x=2 | | (b/7)+(1/4)=19 | | 31+119+x=150 | | -3.4+v/5=-15.9 | | 4(x-6)+4=6x+2(x-6) | | –(7x–2+12)+(-5x–3x+4)=–(-x+7)–(6x–4–7) | | 6(-3)+3y=9 | | 2x2+19x+9=0 | | 2=3x=19/5 | | 2x+7-24=100+4x | | 5(x-2)+6x=7x+4(x-6) | | s/9+26=29 | | –11g=18−20g | | N2/5+2n/6=12 | | (5x-15)+(8x-8)=180 | | 16d=14d+18 | | m/7+40=46 | | 186-w=232 | | 6(9+x)=54 | | 9000m=2700 | | 2x2+x+1=0 | | 5s-4s=17 | | 16=b/7+13 | | 7x–10x=9 | | b+13/4=9 | | -(18-4x)=18 | | 17x=-51;x=-3 | | 85=9d+4 | | 9(k+1)=90 |

Equations solver categories